THE SYSTEM APPROACH AND PROBLEMS OF MODELING NATURAL-TECHNOGENIC SAFETY - Yakub E. Dadaev; Samart D. Hazhmuradova (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 3, Èkonomika,Èkologiâ, 2019)
The paper substantiates the necessity of using the system analysis as an effective tool for studying security problems, in particular the problems of ensuring natural and man-made safety, in the study of natural and anthropogenic threats. The article shows the interrelation and interdependence of natural and man-made safety factors, which is confirmed at the fundamental level today. The article identifies the main types of natural- anthropogenic hazards, such as those of natural, man-made, social character. To study the problems of natural and man-made safety, the model of an ecological-technogenic system is proposed, which adequately reflects the main processes that determine the problems of natural and man-made safety; the specificity of the system approach to problems of natural and man-made safety is determined. This model allows us to classify the risks of the complex system operation. The article, using the methodology of system analysis, highlights the most important methodological principles to be followed when exploring ecological and man-made systems as well. They are: the principle of optimal simplicity, the principle of social responsibility, the principle of interdisciplinarity of the ecological-technogenic system, the principle of objectivity, the principle of hierarchy of goals, the principle of values and “economic realism”, the principle of analysing of constantly developing systems, the principle of system synthesis. The author formulates the main stages of the system analysis of natural and technological safety problems. The author concludes that developing the fundamentals of risk-based analysis of emergency situation consequences requires a special attention.